Penggunaan Kosakata pada Tuturan Anak Penderita Down Syndrome di SLB Negeri 1 Makassar - Pebrianti, Ina; Sultan, Sultan; Wijayanti, Tuti (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2025)
This study aims to: 1) describe the vocabulary use of children with Down Syndrome in communicating at SLB Negeri 1 Makassar; and 2) analyze the factors that influence the use of the vocabulary. This study uses a descriptive qualitative approach with data collection techniques through observation and interviews with two students with Down Syndrome, as well as a teacher at SLB Negeri 1 Makassar. The results show that the vocabulary used by students is dominated by simple nouns related to daily needs, such as books, shoes, and piggy banks. In addition, the initial use of verbs, adjectives, and question words is beginning to appear. Basic vocabulary is the most frequently used form, but the use of affixed and compound vocabulary is also found, although the pronunciation is not yet perfect. Factors that influence children's vocabulary development include age, education, social environment, media and technology, personal experiences, and culture. Older children who receive specific intervention or therapy show a wider variety of vocabulary. The findings of this study are significant for education and speech therapy, particularly in designing language learning strategies tailored to the needs of children with Down syndrome. These findings provide a concrete picture of the forms and patterns of vocabulary acquisition in children with special needs, thus providing a basis for developing more adaptive, communicative learning methods that focus on the individual child's potential.